1986
DOI: 10.1029/ja091ia09p10055
|View full text |Cite
|
Sign up to set email alerts
|

ULF signatures of the polar cusp

Abstract: Geomagnetic pulsations associated with the polar cusp have been detected at Cape Parry, Northwest Territories, Canada, using flux gate and induction magnetometers. Data from this station show enhanced power almost every day near local noon. It is this enhancement which is taken as the signature of the polar cusp. Maximum signal levels are observed prior to local noon, although the signals are present for several hours on each side of local noon. The spectrum of pulsations near the cusp is broadband, reaching f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 24 publications
(14 reference statements)
8
51
0
Order By: Relevance
“…On the other hand, Engebretson et al (1986), extended the analysis of South Pole observations to nighttime intervals for all of 1983 and found also evidence for a secondary maximum of the wave activity (1±80 s) between 2100 and 0200 MLT. Some correspondence for similar results in the Northern hemisphere was provided by Olson (1986), who examined Cape Parry observations (74.8°N, 273 days of data during 1983) and found a broad band increase in the ULF spectra (Pc3±Pc5) around magnetic noon (with maximum values typically encountered before noon) and a minor amplitude maximum in the nighttime hemisphere, in connection with substorms. At lower frequencies (180±420 s), Troitskaya (1985) found, at latitudes of $78…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, Engebretson et al (1986), extended the analysis of South Pole observations to nighttime intervals for all of 1983 and found also evidence for a secondary maximum of the wave activity (1±80 s) between 2100 and 0200 MLT. Some correspondence for similar results in the Northern hemisphere was provided by Olson (1986), who examined Cape Parry observations (74.8°N, 273 days of data during 1983) and found a broad band increase in the ULF spectra (Pc3±Pc5) around magnetic noon (with maximum values typically encountered before noon) and a minor amplitude maximum in the nighttime hemisphere, in connection with substorms. At lower frequencies (180±420 s), Troitskaya (1985) found, at latitudes of $78…”
Section: Introductionmentioning
confidence: 92%
“…At latitudes of the order of 74°±75°and in both hemispheres (Engebretson et al, 1986;Olson, 1986) the pulsation power showed peak values around magnetic noon (with maximum values typically encountered before noon) and a minor amplitude maximum in the nighttime hemisphere, which were attributed to the proximity of cusp and dayside aurora and to the nightside polar expansion of auroral substorms, respectively (Arnoldy et al, 1986;Engebretson et al, 1986): in this sense, the absence of the nighttime power enhancement at TNB might be reasonably interpreted in terms of a negligible substorm in¯uence at $80 on the Pc3 and Pc4 power. The results of recent investigations, although at lower frequencies, can be considered consistent with the present scenario: indeed, Lanzerotti et al (1999), who examined geomagnetic¯uctuations at $5 mHz, found dramatic dierences between 75°and 80°and also remarked that the spectral features associated at $75 with the southward turning of the IMF did not ®nd correspondence at higher geomagnetic latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Many different phenomena such as broadband noise, Pi2 pulsations, Pc4 and Pc5 pulsations, and also transient events like magnetic impulse events (MIEs) and substorm expansions must be expected to contribute. On the other hand, the ULF wave power at the high-latitude dayside has been specifically described as broadband waves (or noise) by previous authors, with a high correlation between the power in the Pc3, Pc4, and Pc5 frequency bands [i.e., Olson, 1986;Kleymenova et al, 1985;Engebretson et al, 1995Engebretson et al, , 1998], and such a phenomenon would be adequately monitored by the simple spectral band power used here. Substorms are known to occur mainly at the nightside, but at least at auroral latitudes and in the early morning hours, we must expect some contribution from these, both from the associated Pi2 pulsations [Olson and Rostoker, 1975] In any case, in the context of deriving a long-term proxy for v, the main justification of the present method is the results it produces.…”
Section: Datamentioning
confidence: 99%
“…We have therefore decided to base the investigation on 1 min data, although it limits the frequency range considerably. On the other hand, the cusp pulsations have been specifically described as broadband noise [i.e., Engebretson et al, 1995] with a high correlation between the power in the Pc3, Pc4, and Pc5 bands [Olson, 1986;Wolfe et al, 1987], so the low time resolution does not have to be a serious limitation.…”
Section: Datamentioning
confidence: 99%
“…For high latitudes (auroral oval and polar cap regions), the presence of a near magnetic noon enhancement of geomagnetic pulsation power in the low-frequency (Pc3-Pc5; 10-600 s periods) intervals is usually considered to be related to the effect of the magnetospheric cusp region, where several mechanisms are active for generating hydromagnetic waves [e.g., Olson, 1986;Engebretson et al, 1995;Ballatore et al, 1996]. When an enhancement of low-frequency geomagnetic power is observed near magnetic midnight, it can be related to the occasional transit of the station under closed field lines [Gupta, 1975] In addition to the above-cited mechanisms for the origin of geomagnetic pulsation power, it is worth mentioning that at all latitudes the geomagnetic pulsation Copyright 1998 by the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%